Revision of the penthimiine leafhopper genus Tambila Distant (Hemiptera: Cicadellidae: Deltocephalinae) of the Indian subcontinent - Shobharani, M.; Viraktamath, C.a.; Webb, M.d. (Zootaxa, 2018)
The genus Tambila Distant of the deltocephaline tribe Penthimiini of the Indian Subcontinent is revised. Tambila opulenta Distant is placed as a junior synonym of Tambila greeni Distant and Tambila gravelyi Distant as a junior synonym of Tambila majuscula (Distant). All valid taxa are redescribed, illustrated and a key to the eight known species from the subcontinent is included. A new record is given for T. gravely from Mauritius (on mango).